Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1063/1.4902993
|View full text |Cite
|
Sign up to set email alerts
|

Low secondary electron yield engineered surface for electron cloud mitigation

Abstract: Secondary electron yield (SEY or δ) limits the performance of a number of devices. Particularly, in high-energy charged particle accelerators, the beam-induced electron multipacting is one of the main sources of electron cloud (e-cloud) build up on the beam path; in radio frequency wave guides, the electron multipacting limits their lifetime and causes power loss; and in detectors, the secondary electrons define the signal background and reduce the sensitivity. The best solution would be a material with a low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 19 publications
1
69
0
Order By: Relevance
“…In our first paper on the discovery of LASE surfaces for e-cloud mitigation we have shown the importance of microstructure grooves and pyramids [23]. In this work we have demonstrated that submicron and nanostructures also play an important and significant role in suppression of SEY and that various lasers can be used to produce these submicron and nano-structures.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In our first paper on the discovery of LASE surfaces for e-cloud mitigation we have shown the importance of microstructure grooves and pyramids [23]. In this work we have demonstrated that submicron and nanostructures also play an important and significant role in suppression of SEY and that various lasers can be used to produce these submicron and nano-structures.…”
Section: Discussionmentioning
confidence: 80%
“…During the laser treatment the laser irradiation leads to material removal (e.g., ablation) and eventually to the formation of micro-, submicron and nano-structures. In our earlier work the main emphasis was put on microstructures (pyramids and grooves) [23], but the results presented above demonstrated the importance of submicron and nano-structures. As can be seen in the SEM images in this study, LASE has induced the grooves with tens of microns depth (microstuctures) and the groove walls are covered with submicron and nano-spheres or/and nano-wire structures.…”
Section: Discussionmentioning
confidence: 99%
“…These will be applied through a combination of ex situ and in situ coatings, either for the new focusing magnets in the highluminosity interaction regions (IR1 and IR5) or for retrofitting of the existing ones in the low-luminosity interaction regions (IR2 and IR8) [7]. Laser-engineered surface structures (LESS) [8,9] produced on the copper surfaces facing the beam are also being considered as a possible option to reduce the SEY, due to their potential for in situ implementation [10], mandatory for retrofitting. Both these surface treatments have been tested and validated on 2.2-m-long beam screens installed in the cold bore experiment (COLDEX) facility at the CERN SPS [11,12], showing, in particular, their robustness after several thermal cycles from room to cryogenic temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The electron cloud is a key problem in particle accelerators, which can cause the degradation of beam quality and limit the performance of particle accelerators with high energy, high intensity, high luminosity and long beam lifetime [1][2][3][4][5][6][7][8]. The methods of mitigating electron cloud effect have been studied by many researchers from several organizations, such as CERN [9,10], STFC [11,12], NSRL [13], KEK [7,14], INFN [15], etc. C. Yin Vallgren et al found that a complete suppression of e-cloud can be achieved by amorphous carbon coating of liners [9].…”
Section: Introductionmentioning
confidence: 99%
“…Yusuke Suetsugu et al tested the effectiveness of antechambers and TiN coating for the inhibition of electron cloud [14]. Valizadeh et al proposed laser engineered surface technology to obtain low SEY surface [11,12]. After laser treatment, the SEY of stainless steel, copper, and aluminum can be reduced to less than 1.…”
Section: Introductionmentioning
confidence: 99%